2018
DOI: 10.1039/c8sc03339k
|View full text |Cite
|
Sign up to set email alerts
|

Redox-triggered cascade dearomative cyclizations enabled by hexafluoroisopropanol

Abstract: Aromatization as the driving force to initiate hydride transfer addressed the drawbacks of hydride transfer-involved reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(25 citation statements)
references
References 81 publications
0
25
0
Order By: Relevance
“…[24b] These two reactions, however, both still suffered from the drawbacks such as tedious preparation of substrates and employment of transitional metallic catalysts. As a continuation of our research interest in developing redox-neutral cascade reactions for the rapid construction of privileged heterocyclic skeletons, [25] herein, we reported a practical and environmentally benign cascade protocol for the syntheses of privileged DHBTDs via the Lewisacid-catalyzed cascade condensation/[1,7]-hydride transfer/cyclization process from aldehydes and 2-aminobenzenesulfonamides readily accessed by S N Ar reaction [26] (Scheme 1d). Compared with conventional methods, this method has fascinating advantages such as novel substrate skeletons, broad substrate scope, [1,7]-HT manner, metal-free condition and with water as the only by-product as well as the facile introduction of aryl, heteroaryl, allyl and propargyl groups etc.…”
mentioning
confidence: 99%
“…[24b] These two reactions, however, both still suffered from the drawbacks such as tedious preparation of substrates and employment of transitional metallic catalysts. As a continuation of our research interest in developing redox-neutral cascade reactions for the rapid construction of privileged heterocyclic skeletons, [25] herein, we reported a practical and environmentally benign cascade protocol for the syntheses of privileged DHBTDs via the Lewisacid-catalyzed cascade condensation/[1,7]-hydride transfer/cyclization process from aldehydes and 2-aminobenzenesulfonamides readily accessed by S N Ar reaction [26] (Scheme 1d). Compared with conventional methods, this method has fascinating advantages such as novel substrate skeletons, broad substrate scope, [1,7]-HT manner, metal-free condition and with water as the only by-product as well as the facile introduction of aryl, heteroaryl, allyl and propargyl groups etc.…”
mentioning
confidence: 99%
“…Pleasingly, the initial test showed that the alcohol 1a could be converted to the desired five‐membered cyclic ether 2a under the irradiation of blue strip light emitting diode (LEDs) at room temperature (entry 1). Among the various solvent systems, hexafluoroisopropanol (HFIP) that has distinctly acidic properties and strong hydrogen‐bond donor ability was found to be a suitable solvent in this reaction (entry 2) 36 . More promising results were obtained when the amount of NIS was slightly increased (entries 3–6).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, our group disclosed an unprecedented cascade hydride transfer/dearomative cyclizations for one‐step construction of structurally diverse polycyclic amines (Scheme ) . Thanks to the aggregate effect of HFIP, phenols 80 could interact with o ‐aminobenzaldehydes 81 via a cascade dearomatization/rearomatization/dearomatization sequence.…”
Section: Dearomatization Reactionsmentioning
confidence: 99%
“…Recently, our group disclosed an unprecedented cascade hydride transfer/dearomative cyclizations for one-step construction of structurally diverse polycyclic amines (Scheme 27). [48] Thanks to the aggregate effect of HFIP,…”
Section: Dearomatization Reactionsmentioning
confidence: 99%